A longitudinal study of well‐being in older workers and retirees: The role of engaging in different types of activities. Issue 4 (8th January 2013) - Potočnik, Kristina; Sonnentag, Sabine
Abstract : This study examines the impact of engaging in seven types of activities on depression and quality of life in retirees and older workers over a period of 2 years, using a sample from the survey of health, ageing and retirement in Europe. Longitudinal data were available from 2, 813 retirees and 1, 372 older employees. Our results showed that volunteering, providing help and going to sports or social clubs at the baseline improved retirees' quality of life over a period of 2 years. No direct effects of engaging in activities were found for older employees. Moreover, higher depression at the baseline fostered the depression experience at the follow‐up in those retirees and older employees who were caring for disabled adults at baseline. In retirees with higher depression at baseline, participation in religious organizations was associated with a greater decrease in depression at follow‐up than in those who had lower levels of depression at baseline. For older employees, taking part in political or community organizations at baseline was related to a greater decrease in depression at follow‐up than in those employees who experienced higher initial depression. Practitioner points: Practitioners should make attempts to reduce physical demands and time pressure exerted over older employees to improve their well‐being over time. Practitioners should design intervention programmes and preventive measures that focus on how to stimulate retirees' and older employees' engagement in community and leisure activities to achieve successful ageing.